Síntese de polímeros supramoleculares derivados dos ácidos palmítico e mirístico com meglumina e suas caracterizações em meio aquoso - Lopes Junior, Marco Antonio [UNESP] (2015)
Currently many researchers have turned their attention to the field of supramolecular chemistry, a relatively new area of chemistry that works with the compounds beyond the atoms, beyond a single molecule, works with the intermolecular interactions, such as van der Waals bonding, hydrophobic interaction, dipole dipole bonding and hydrogen bonding. The studies in this area, especially on supramolecular polymers can propose new techniques for the synthesis of various compounds such as elastomers, supramolecular gels, thermotropic liquid crystals, superhydrophobic surfaces, giant micelles, and many other materials examples. This dissertation demonstrates a simple technique for the synthesis of supramolecular compounds intermolecular interactions formed by self-assembly, using two different carboxylic acids (myristic acid that have fourteen carbons in their structure and palmitic acid that have sixteen carbons in its structure) and the meglumine. Then establish a relationship of carbon chain of the size difference of the acid with the possible formation of supramolecular compounds. The characterization of the compounds was obtained by techniques such as thermogravimetry (TG-DTG), differential scanning calorimetry (DSC), nuclear magnetic resonance (NMR), relative viscosity, calculation of surface tension and the consequent obtaining of the critical aggregation concentration. It was possible to observe the formation of carboxylate-meglumine adducts, the supramolecular polymerization of the compound palmitate-meglumine when in aqueous solution with a concentration above 2% (w/w) and the non-polymerization of myristate-meglumine compound, even at high concentrations such as 50% (w/w). Was also observed that the temperature required to cause the gel-sol transition on the supramolecular polymer palmitate-meglumine in aqueous solution 6% (w/w) is relatively low, around 37.58 ºC.